Effect of Cutting Speed of Carbon Steel ST 41 on Cutting Temperature in Turning Process - Larosa, Albert Hendi Yanto; Lubis, Yakmuri; Hafid, Burhan (International Journal of Mechanical Computational and Manufacturing Research, 2025)
The turning process is one of the most widely used lathe machining techniques in manufacturing, involving the interaction between the machine tool, workpiece, and cutting tool. During cutting, friction between the chisel and the workpiece generates excessive heat, with most cutting energy converted into heat. This study examines the effect of cutting speed on temperature in chisels, chips, and ST41 carbon steel workpieces at various lathe speeds. Using an experimental method, cutting speeds of 260 RPM, 560 RPM, and 800 RPM were tested. Data collected included lathe rotation speed, specimen temperature, chisel temperature, chip temperature, cutting depth, and chip mass. Results show that temperature increases with cutting speed. At 260 RPM, the chisel temperature was 38.46°C, the workpiece 36.83°C, and the chip 36.21°C. At 800 RPM, the highest tool temperature was 65°C, the workpiece reached 62.33°C, and the chip 48.56°C. This indicates that higher cutting speeds generate more heat, making the turning process more thermally intensive.